Sitosterolemia With Atherosclerosis in a Child: A Case Report - Ba, Hongjun; Peng, Huimin; He, Xiufang; Cheng, Liangping; Lin, Yuese; Li, Xuandi; Wang, Huishen; Qin, Youzhen (Frontiers in Pediatrics, 2021)
Introduction: Sitosterolemia is a rare condition in children and is often misdiagnosed as familial hypercholesterolemia. Serious complications can result if not treated promptly and effectively. When pediatric patients are diagnosed with sitosterolemia, vascular and cardiac studies are important to evaluate for the presence of atherosclerosis. Few cases of severe atherosclerotic heart disease in children with sitosterolemia have been reported, making this case worthy of presentation. Case Presentation: Here, we report a case of sitosterolemia in an 8-year-old child. The patient presented with severe hypercholesterolemia and xanthoma. He was diagnosed two and a half years prior with familial hypercholesterolemia because his father had elevated cholesterol levels. After conventional treatment, the patient was dissatisfied with lipid level control and visited our hospital for further management. Genetic tests of the patient and parents found mutations in intron 7 (NM 022436.2, c.904+1G>A) and intron 9 (NM 022436.2, C. 1324+1de1G) of ABCG5. The 7 intron mutations were from his mother, and the 9 intron mutations were from his father. The patient was diagnosed with sitosterolemia. Results: The child was treated with ezetimibe, a low plant sterol diet, and clopidogrel anticoagulant therapy. After 3 months of treatment, the blood lipid level was significantly lower. Conclusion: Genetic testing should be completed as soon as possible to avoid misdiagnosis in children with abnormally elevated hypercholesterolemia who have a family history of elevated cholesterol. In addition, clinicians should rule out great arteritis and be vigilant in evaluating patients for systemic arterial disease and atherosclerosis.